Sport and the media : managing the nexus - Nicholson, Matthew; Kerr, Anthony;Sherwood, Merryn (London, United Kingdom : Routledge, 2015)
Sport and the media is an essential textbook for any degree level course on sport and the media, sport media management or sport communication, and invaluable reading for any sport media or sport management practitioner looking to improve their professional skills.
Part 1 : Sport media foundations -- Part 2 : Sport media landscapes -- Part 3 : Sport media professionals -- Part 4 : Sport media strategies
Includes bibliographical references and index.
Keywords: MASS MEDIA AND SPORTS